Pembelajaran Bahasa Arab dengan Pemanfaatan Teknologi - Rahmat Iswanto (Arabiyatuna: Jurnal Bahasa Arab, 2017)
This article examines how technology can be utilized in the process of Arabiclearning. Many problems of learning of Arabic language in accordance with the context faced in various educational institutions, a teacher allows modification formethodsof teaching and learning. This can be done with technological developments that contain lots of information that can be used to improve learning outcomes. Discussion about the application of technology in learning Arabic contains the question of what kind of technology that can be utilized, whether the technology can play a role in the alignment and sustainability of learning Arabic from basic to middle level, whether the technology can make learners will be more interested in learning the Arabiclanguage, whether the technology can create realization and relevance to what the students perceived, whether the technology can create Arabic learning media more varied that still lacks, whether the technology can improve the ability or competence of teachers in teaching Arabic, whether technology is able to take advantage of time allocation for learning Arabic, whether the technology is able to create an Arabic speaking environment. Through qualitative descriptive method, this article summarizes some of the above questions.